The 21st‐Century Dental Curriculum: A Framework for Understanding Current Models. Issue 8 (1st August 2017) - Kassebaum, Denise K.; Tedesco, Lisa A.
Abstract : This article provides an overview of the emergence of professional education and academic dentistry, in particular into the comprehensive research university. The development of academic dentistry as a vital member of the academic health center at the research university and beyond is described. Summaries are provided of major studies and innovations in dental education models and curricula, ranging from the Gies report in 1926 to the 1995 Institute of Medicine study Dental Education at the Crossroads, the U.S. surgeon general's report on oral health in 2000, the Macy study report in 2008, and the American Dental Education Association Commission on Change and Innovation in Dental Education (ADEA CCI) series of articles published from 2005 to 2009. The article also tracks changes in number and institutional affiliation of U.S. dental schools. This article was written as part of the project "Advancing Dental Education in the 21 st Century."